THE STUDENTS’ VOICES ON GAMIFICATION USING QUIZIZZ APPLICATION IN GRAMMAR CLASSES AT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Mustaqim, Afifah Maghfirah; Abdul, Nurdevi Bte.; Muhsin, Muh. Arief (Journal of Computer Interaction in Education, 2024)
This research aimed to find out the students’ voices toward Gamification using Quizizz in grammar classes at Universitas Muhammadiyah Makassar. This research used descriptive quantitative method. The data was collected through online questionnaire and presented in descriptive and numerical form. The population were the 7th semester students, namely 7D, 7E, and 7F of English Education Department at Universitas Muhammadiyah Makassar and the sample were the 10 students from each class of the population. The sampling technique used in this research was purposive random sampling technique. This research findings showed that the students voices based on questionnaire’s answer toward the used of Quizizz in grammar classes. the result showed most of the students chose agreed on the positive statements and chose disagreed on the negative statements. The total highest mean score in terms of stimulation aspect was 4.47, attractiveness aspect was 4.40, perspicuity aspect was 4.27, and dependability aspect was 4.17. It means that students have a good voice toward Quizizz in grammar classes activities. Based on the findings, it can be concluded that Gamification using Quizizz in grammar classes was approved by the students in English Education Department at Universitas Muhammadiyah Makassar.